2023
DOI: 10.1364/ol.482936
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-radiation enhancement of sensing properties of FBGs in a few-mode polymer CYTOP fiber

Abstract: We investigate the effect of γ-radiation on temperature (T) and relative humidity (RH) sensitivities of polymer perfluorinated fiber Bragg gratings (FBGs). To this aim, different γ-radiation doses (80, 120, 160, and 520 kGy) were applied to a set of FBGs. We show that irradiated FBGs demonstrate an RH sensitivity rise with the received dose: from 13.3 pm/%RH for a pristine FBG up to 56.8 pm/%RH for a 520-kGy dose at 30℃. In contrast, T sensitivity decreases with radiation dose with a subsequent change of sign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…POF has the benefit of an easy connection and a large core, which could be an economic solution for the in-home network. Different kinds of materials are implemented for POF fabrication, such as polymethyl methacrylate (PMMA) [ 3 , 4 ], polydimethylsiloxane (PDMS) [ 5 , 6 ], polycarbonate (PC) [ 7 , 8 ], polystyrene (PS) [ 9 , 10 ], perfluorinated polymer (commercially known as CYTOP ® (AGC, Inc., Tokyo, Japan) [ 11 , 12 ], cycloolefin polymer (commercially known as ZEONEX ® *ZEON (Corporation, Tokyo, Japan)) [ 13 , 14 ], and cycloolefin copolymer (commercially known as TOPAS ® ) (TOPAS Advanced Polymers, Farmington Hills, MI, USA) [ 15 , 16 ]. The flexibility of POF material allows for the production of POFs with varying specifications or materials to meet the needs of various applications.…”
Section: Introductionmentioning
confidence: 99%
“…POF has the benefit of an easy connection and a large core, which could be an economic solution for the in-home network. Different kinds of materials are implemented for POF fabrication, such as polymethyl methacrylate (PMMA) [ 3 , 4 ], polydimethylsiloxane (PDMS) [ 5 , 6 ], polycarbonate (PC) [ 7 , 8 ], polystyrene (PS) [ 9 , 10 ], perfluorinated polymer (commercially known as CYTOP ® (AGC, Inc., Tokyo, Japan) [ 11 , 12 ], cycloolefin polymer (commercially known as ZEONEX ® *ZEON (Corporation, Tokyo, Japan)) [ 13 , 14 ], and cycloolefin copolymer (commercially known as TOPAS ® ) (TOPAS Advanced Polymers, Farmington Hills, MI, USA) [ 15 , 16 ]. The flexibility of POF material allows for the production of POFs with varying specifications or materials to meet the needs of various applications.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works [7][8][9], we demonstrated that gamma radiation treatment changes the climatic properties of CYTOP FBGs: we observed a rise of the RH sensitivity with received dose and a decrease of temperature sensitivity with subsequent change of sign from positive to negative. Among irradiation doses, which we applied in the experiment, the dose of 200 kGy provided the closest to zero temperature sensitivity of the irradiated FBGs [7,8]. This case is prospective for RH sensing since temperature cross-sensitivity can be eliminated.…”
Section: Introductionmentioning
confidence: 62%
“…However, practical realization of RH sensors requires temperature crosssensitivity elimination. A certain optimal fiber pre-strain [6] and gamma irradiation of FBGs of up to optimal dose [7][8][9] are potential solutions recently proposed for CYTOP ® FBGs.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the above into account, we excluded the sensitivity of the FBG with a 520 kGy received dose from a linear approximation. Irradiated FBGs demonstrate not only a decrease of temperature sensitivity, but also a rise of RH sensitivity [22]. It rises from 13.3 pm/%RH for pristine FBG up to 56.8 pm/%RH for the case of 520 kGy dose.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, we tested irradiated FBGs in the environmental chamber and we found that gamma radiation increases the sensitivity of perfluorinated FBGs to relative humidity (RH) and decreases their temperature sensitivity. In particular, among the applied dosed of 80, 120, 160 and 520 kGy, the FBG irradiated up to 160 kGy demonstrated the closest to zero temperature sensitivity [22]. This case is attractive for RH sensing since the temperature cross-sensitivity is minimized.…”
Section: Introductionmentioning
confidence: 85%